Assessing the Impact of TLR4 rs4986790 Polymorphism on Bacterial Meningitis Risk: A Systematic Review and Meta-Analysis - Praveen Kumar Chandra Sekar; Ramakrishnan Veerabathiran (Annals of Indian Academy of Neurology)
Background and Objectives: Toll-like receptor (TLR2) gene plays an important role in the pathogenesis of bacterial meningitis (such as meningococcal meningitis and pneumococcal meningitis). The association between TLR4 rs4986790 polymorphism and the susceptibility to bacterial meningitis has been extensively studied. However, the results of these studies remain inconsistent. Therefore, we performed a meta-analysis to evaluate the association between TLR4 rs4986790 polymorphism and the susceptibility to meningococcal meningitis and pneumococcal meningitis. Methods: Google Scholar, Embase, and PubMed databases were searched for case–control studies on TLR4 polymorphisms and the risks of meningococcal meningitis and pneumococcal meningitis, published up to May 31, 2024. To assess the strength of the association between TLR4 polymorphism and meningococcal meningitis and pneumococcal meningitis, the odds ratios (ORs) with 95% confidence intervals (CIs) were used. The meta-analysis of the associations between the TLR4 rs4986790 polymorphism and meningococcal meningitis and pneumococcal meningitis was carried out under different genetic models. Meta-analyses were conducted using Cochrane RoB 2 tool and Metagenyo to calculate the ORs and 95% CIs. Fourteen published studies with 3599 cases and 7438 controls were included. Results: Overall, there was a strong correlation between TLR4 polymorphisms and meningococcal meningitis observed across three genetic models using a random-effects model: GG + GA vs. AA (OR: 0.34, 95% CI: 0.14–0.79, P = 0.01, I² = 60%); GA vs. AA (OR: 0.34, 95% CI: 0.13–0.91, P = 0.03, I² = 65%); and GG vs. AA (OR: 0.34, 95% CI: 0.14–0.78, P = 0.01, I² = 59%). Conversely, a fixed-effects model also revealed a significant association in the G vs. A model (OR: 0.84, 95% CI: 0.73–0.96, P = 0.01, I² = 38%). In pneumococcal meningitis, a fixed-effects model analysis demonstrated a significant association in the GG vs. AA model (OR: 0.35, 95% CI: 0.14–0.87, P = 0.02, I² = 48%) respectively. Conclusion: This meta-analysis showed a strong correlation between TLR4 rs4986790 polymorphism and susceptibility to meningococcal meningitis and pneumococcal meningitis. Further studies with diverse populations are needed to validate and strengthen these findings.